The Doctrine of Belief as a Vulnerable Group: How do the Human Rights Laws Accommodate this Group? - Desika Arum Sari (Universitas Negeri Semarang, 2019)
One of the important issues that the global nature of human rights is the emergence of the idea and practice of multiculturalism, that is a willingness to coexist with other people or groups differntly. Multiculturalism is essentially an willingness of accept others groups equally as unity without care about cultural differences, ethnic, gender, language, or religion. The new legal problems are the most crucial in Indonesia as a result of multiculturalism is a matter of religion and belief. Remember that Indonesia has some same religion and belief, which its people have strongs beliefs about religion and beliefs of each of them. The implementation of Act Number 39 of 1999 on human rights towards the protection of vulnerable groups to the residents of Pangudi Rahayuning Bawana Organization in Semarang is trust less. There are some human rights that have not been fulfilled, namely related to the exitance of a religious column discharge or fill the column by selecting among them the religions of six official religion. The contraint factors by the Pangudi Rahayuning Bawana organization to a fulfillment of his civil rights is freedom of religion and belief, marriage, funerals, the right to establish places of worship and the right to obtain religious education in according with the religion and beliefs for their children in according with his beliefs.